TANTANGAN PENINGKATAN PENERAPAN SAK EMKM PADA UMKM DI BANYUWANGI - Novilia Kareja; Nurul Alfiyah; Shinta Setiadevi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study was conducted to describe the efforts that can be made to improve the application of SAK EMKM to SMEs in Banyuwangi. The current condition is that there is no financial recording and separation of financial management in the MSMEs. This research is qualitative research conducted with a descriptive approach. Identification of limitations in the application of SAK EMKM is explored and put forward to be able to determine a series of efforts that can be used to improve the application of SAK EMKM. Some ideas are presented as an illustration of the forms of efforts that can be made to increase the application of SAK EMKM and build a culture of financial reporting in MSMEs based on agency theory and signal theory. The culture of presenting financial reports and the application of SAK EMKM cannot be grown and developed without the participation and support of several related institutions and encouragement from SMEs themselves. The collaboration of each of these elements can encourage the emergence of a willingness to present financial reports to MSMEs based on SAK EMKM.